Are basin and reservoir tillage effective techniques to reduce runoff under sprinkler irrigation in Mediterranean conditions? - Silva, Luis L. (2017)
The increasing use of low pressure moving sprinklers irrigation systems, like center-pivot irrigation systems, has increased surface runoff problems. Runoff decreases the irrigation system application efficiency, increasing the operational costs. It can also be responsible for environmental problems, such as soil erosion and the contamination of surface waters. Basin tillage and reservoir tillage have proved to be an effective practice to prevent runoff in many situations and can be an option to reduce surface runoff under moving sprinkler irrigation systems operating in Mediterranean conditions. However, even though it is a common practice in some Mediterranean regions, there are very few studies quantifying the effect of these tillage practices under moving sprinkler irrigation systems in Mediterranean countries. Many farmers are still not convinced that this is the best practice to prevent runoff. Some of them are converting to conservation agriculture, using no-till or minimum tillage, but the results of these tillage systems in the prevention of runoff are not always consistent. The industry is also creating new implements used to create the basins and reservoirs that apparently have some advantages over the old ones. But more studies are still required in order to be able to identify the better solutions for different soil, crop and irrigation management situations.